2003
DOI: 10.1002/ijc.11008
|View full text |Cite
|
Sign up to set email alerts
|

Profile of gene expression induced by the tumour promotor TPA in murine epithelial cells

Abstract: Malignant transformation of mouse skin by chemical carcinogens and tumour promoters, such as the phorbol ester 12-O-tetradecanoylphorbol-13-acetate (TPA), is a multistage process that leads to squamous cell carcinoma (SCC) formation. In an effort to identify tumour-associated genes, we studied the influence of short-term TPA-treatment on the gene expression profile of murine skin. A comprehensive microarray with some 5,000 murine gene specific cDNA fragments was established and hybridised with pooled RNA deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 73 publications
8
57
1
Order By: Relevance
“…Indeed, a feedback mechanism maybe established whereby anomalous ROCK2/p-Mypt1/MLC-mediated changes in local ECM, increase tissue rigidity via altered integrin/FAK/β-catenin signalling and in turn necessitate ROCK2/p-Mypt1-regulated changes in actinomyosin/MLC expression to provide the motility necessary for transformed cells to invade tissues with increased rigidity. 6,13,28,30 Collectively these data demonstrate that in the appropriate context of late-stage, highly proliferative p53 -ve /p21 +ve /NF-κβ +ve papillomas, ROCK2 activation co-operates with ras Ha activation to induce malignant conversion. Further ROCK2 and ROCK associated-NFκβ are required to maintain malignant progression to SCC, alongside Mypt1 inactivation/and tenascin c mediated changes in the ECM/motility that facilitate invasion.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Indeed, a feedback mechanism maybe established whereby anomalous ROCK2/p-Mypt1/MLC-mediated changes in local ECM, increase tissue rigidity via altered integrin/FAK/β-catenin signalling and in turn necessitate ROCK2/p-Mypt1-regulated changes in actinomyosin/MLC expression to provide the motility necessary for transformed cells to invade tissues with increased rigidity. 6,13,28,30 Collectively these data demonstrate that in the appropriate context of late-stage, highly proliferative p53 -ve /p21 +ve /NF-κβ +ve papillomas, ROCK2 activation co-operates with ras Ha activation to induce malignant conversion. Further ROCK2 and ROCK associated-NFκβ are required to maintain malignant progression to SCC, alongside Mypt1 inactivation/and tenascin c mediated changes in the ECM/motility that facilitate invasion.…”
Section: Discussionmentioning
confidence: 76%
“…1,2,13 Previous K14.ROCK er studies demonstrated ROCK-associated collagen deposition resulted in a stiffened ECM and increased tissue rigidity. 5 Similarly human cutaneous SCCs demonstrated ROCK2/p-Mypt1 staining correlated with MLC2 phosphorylation and actomyosin contractility; 6 suggesting a mechano-transduction pathway facilitated progression by providing the mobility/flexibility necessary to invade tissues with increased rigidity, [6][7][8] ideas supported by analysis of tenascin C [28][29][30] and p-Mypt1 inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a dimethylbenz(a)anthracene (DMBA)/12-O-tetradecanoylphorbol-13-acetate (TPA)-induced skin carcinogenesis model, carcinogen-induced skin cancer formation is severely impaired by treatment with antagonistic TNF-␣ Abs or in the absence of host TNF-␣ and TNF-␣ signaling (17)(18)(19). Most notably, the TPA-induced promotion phase of tumor formation, characterized by epigenetic alterations in gene expression, is most significantly affected by the absence of endogenous TNF-␣, and SLPI was identified as one of the genes most prominently induced by TPA in the dorsal skin and with very high expression levels in advanced stages of DMBA/TPA-induced skin tumors (20). Similarly, in an inflammation-associated model of liver cancer, treatment with antagonistic TNF-␣ Abs resulted in apoptosis of transformed hepatocytes and failure to develop hepatocarcinomas (21).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were diluted in DigEasyHyb (Roche Diagnostics, Mannheim, Germany) and hybridized to microarray slides for 16 h at 371C under gentle agitation. Thereafter, the slides were washed at room temperature with: (i) 1 Â SSC/ 0.1% (w/v) SDS; (ii) 0.1 Â SSC/0.1% SDS for 5 min; (iii) 70% ethanol for 30 s; (iv) 100% ethanol for 30 s; and (v) finally airdried (Schlingemann et al, 2003). To account for the systemic error caused by different properties of the fluorescent dyes concerning incorporation, mean brightness and background noise, the hybridizations were always performed in duplicate experiments with interchanged assignment of fluorescent dyes ('color switch').…”
Section: Labeling and Hybridization Of Samplesmentioning
confidence: 99%